Waste Management of Ege University during the COVID-19 period - S. Tugce Daglioglu; Simge Sertkaya; Armagan Kinal; Melike Bor; Dincer Ayaz (Journal of Sustainability Perspectives, 2022)
Ege University manages packaging wastes, hazardous wastes, electronic wastes and organic wastes within the scope of integrated waste management and has been awarded the Ministry of Environment and Urbanization Zero Waste Certificate. For packaging waste, recycled and non-recyclable wastes are collected separately. Recycled wastes are collected in blue boxes and gray boxes are used for non-recyclable wastes. Along with the pandemic period, with the directive of the Ministry of Environment and Urbanization, extra gray boxes were added and used to collect waste materials such as masks, gloves, etc. The first COVID case in Turkey started in March 2020 and these studies came into effect in April. In this context, all staff and students are informed and the health of the community and the environment is protected.Keyword: waste management, mask and glove waste management, COVID-19